Agentywne znaczenie formantu -wa w gwarach wielkopolskich i języku polskim na tle innych języków słowiańskich - Błażej Osowski (Ksiegarnia Akademicka Publishing, 2014)
Agentive meaning of the -wa suffix in Greater Polish dialects and general Polish versus other Slavic languages